The Use of The Mondly Arabic Application in Increasing Mastery of Muĥādatsah Santri Takhasshush Al Urwatul Wutsqaa Islamic Boarding School, Sidrap Fortress - Firman, Firmansyah; Herdah; Saepudin (Al-Iftah: Journal of Islamic studies and society, 2022)
This study discusses the use of the Mondly Arabic Application in Improving Mastery of Muĥādatsah Santri Takhasshush Al Urwatul Wutsqaa Islamic Boarding School, Fort Sidrap. This study aims to determine the use of the Mondly Arabic Application in Improving Mastery of Muĥādatsah Santri Takhasshush Al Urwatul Wutsqaa Islamic Boarding School, Fort Sidrap. This study used a quasi Experimental Design in the form of a Pretest-Posttest Control Group Design. The location for the research was Al Urwatul Wutsqaa Islamic Boarding School, Sidrap Fort. The results of this study indicate, (1)masteryMuĥādatsahTakhassush students at PP Al Urwatul Wutsqaa Benteng-Sidrap using Mondly Arabic have an average mean of 86.00. This indicates that there is an increase in Muĥādatsah mastery of 22.80. (2) students takhassush Muĥādatsah mastery in PP Al Urwatul Wutsqaa Benteng-Sidrap using conventional media has an average mean of 73.40. This indicates that there is an increase in Muĥādatsah mastery of 18.00. (3) the mastery of Muĥādatsah takhassush students at PP Al Urwatul Wutsqaa Benteng-Sidrap when using Mondly Arabic using conventional media there is a difference with the scoremean posttestexperimental group andmean posttestthe control group obtained 86.00 > 73.40 with a difference of 12.60. It can be interpreted that the final score between the experimental and control groups is different so that there is a positive influence from the independent variables on the dependent variable.